PENGARUH PENGEMBANGAN KARIR DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. INDAH LOGISTIK CARGO PEKANBARU - Muazzan Alamsyah; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The purpose of this study was to determine the influence of careerdevelopment and the commitments made by PT. Logistics Cargo Indah Pekanbaru on theperformance of its employees. PT. Logistics Cargo Indah Pekanbaru is one of the deliveryservice company private commercial enough in the eyes of the people of Indonesia,especially the townspeople. PT. Logistics Cargo Indah Pekanbaru has implemented careerdevelopment and organizational commitment to employees to induce employees to betterperformance in which will be able to cause a sense of employee loyalty to the company.In this case the optimal performance of employees and work in accordance with thestandards of the company will be able to realize the company's goals. In this study, thepopulation is consumers who use the services of PT. Logistics Cargo Indah Pekanbaru asmany as 100 people by distributing questionnaires / questionnaire and interviews.The study concluded that the impact of career development and a commitment toemployee performance in PT. Logistics Cargo Indah Pekanbaru. With evidence of regressioncalculation results show that thitung career development of (5.766)> t table (2.002) and Sig.(0,000) <0.05. What this means is that the variable career development have significantinfluence on employee performance. Then evidenced by the value of the t variable oforganizational commitment (4.017)> t table (2.002) and Sig. (0,000) <0.05. What this meansis that the variable organizational commitment significantly influence employee performance.Keywords: The Influence Of Career Development And Organizational CommitmentAnd Employee Performance.